2017
DOI: 10.1002/ejhf.733
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of right ventricular failure after ventricular assist device implant: systematic review and meta‐analysis of observational studies

Abstract: Right ventricular failure (RVF) after left ventricular assist device (LVAD) implantation is associated with increased morbidity and mortality, but the identification of LVAD candidates at risk for RVF remains challenging. We undertook a systematic review and meta-analysis of observational studies of risk factors associated with RVF after LVAD implant. Thirty-six studies published between 1 January 1995 and 30 April 2015, comprising 995 RVF patients out of a pooled final population of 4428 patients, were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
177
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(200 citation statements)
references
References 52 publications
(64 reference statements)
2
177
1
Order By: Relevance
“…We are grateful to Dr Cerit for his interest in our paper and we concur that atrial rhythm and performance may play important roles in the pathophysiology of right ventricular failure (RVF), specifically in patients referred for left ventricular assist device (LVAD) implant.…”
mentioning
confidence: 61%
“…We are grateful to Dr Cerit for his interest in our paper and we concur that atrial rhythm and performance may play important roles in the pathophysiology of right ventricular failure (RVF), specifically in patients referred for left ventricular assist device (LVAD) implant.…”
mentioning
confidence: 61%
“…Variables identified to predict RV failure after LVAD placement vary widely and reflect the complexity in the multifactorial mechanism of the RV failure onset. While no single best predictor variable has been identified, some form of RV hemodynamics or tricuspid valve function surrogates are most commonly used alone or as part of a predictive risk score .…”
Section: Discussionmentioning
confidence: 99%
“…We chose to use a RVAD as the primary outcome due to varying definitions of RVF at our institutions, many of which are dependent on institutional practice variation in management of inotropes or nitric oxide after CF-LVAD as opposed to an RVAD which is only employed in the sickest cohort of patients with acute severe RVF. Variables identified to predict RV failure after LVAD placement vary widely 1,9,10,14,15 and reflect the complexity in the multifactorial mechanism of the RV failure onset. While no single best predictor variable has been identified, some form of RV hemodynamics 9,10,16 or tricuspid valve function 6,8 surrogates are most commonly used alone 6,[8][9][10]16 or as part of a predictive risk score.…”
Section: Discussionmentioning
confidence: 99%
“…Hemodynamic parameters were not independently associated with residual TR in this study. Because recent studies showed that preoperative pulmonary artery pulsatility index32, 33 and RV stroke work index34, 35 are associated with early right heart failure after LVAD implantation, future studies are needed whether these parameters predict the residual TR in patients with mid‐ to long‐term LVAD support. In addition, ischemic cardiomyopathy tended to have more residual TR in this study, although previous work showed that nonischemic cardiomyopathy is a risk factor for early right heart failure 34.…”
Section: Discussionmentioning
confidence: 99%